The Insulin-Degrading Enzyme from Structure to Allosteric Modulation: New Perspectives for Drug Design - Grazia Raffaella Tundo; Giuseppe Grasso; Marco Persico; Oleh Tkachuk; Francesco Bellia; Alessio Bocedi; Stefano Marini; Mariacristina Parravano; Grazia Graziani; Caterina Fattorusso; Diego Sbardella (Biomolecules, 2023)
The insulin-degrading enzyme (IDE) is a Zn2+ peptidase originally discovered as the main enzyme involved in the degradation of insulin and other amyloidogenic peptides, such as the β-amyloid (Aβ) peptide. Therefore, a role for the IDE in the cure of diabetes and Alzheimer’s disease (AD) has been long envisaged. Anyway, its role in degrading amyloidogenic proteins remains not clearly defined and, more recently, novel non-proteolytic functions of the IDE have been proposed. From a structural point of view, the IDE presents an atypical clamshell structure, underscoring unique enigmatic enzymological properties. A better understanding of the structure–function relationship may contribute to solving some existing paradoxes of IDE biology and, in light of its multifunctional activity, might lead to novel therapeutic approaches.